Locality caching multiroot multigeneration routing algorithm in mobile ad hoc networks - Peng, W.; Zhang, X.; Makki, K. (Proceedings. 12th International Conference on Computer Communications and Networks (IEEE Cat. No.03EX712), 2003)
A locality caching multiroot multigeneration (LCMRMG) routing algorithm for mobile ad hoc networks (MANET). The LCMRMG algorithm extends and significantly enhances a previously proposed single-root MANET routing algorithm. Hosts in a LCMRMG MANET cache the locality of network traffic routing through them. Based on the cached locality statistics, a host can calculate the estimated reduction of network traffic if it becomes a new root router and can elect to do so if the reduction exceeds a predefined threshold value.